التعددية الطائفية و اشكالية بناء الأمن المجتمعي في العراق - - بن بلخير جمال (جامعة المسيلة, 2022)
تناولنا في هذه الدراسة التعددية الطائفية واشكالية بناء الأمن المجتمعي في العراق ، تطرقنا من خلالها الى الاطار المفاهيمي للتعددية الطائفية والامن المجتمعي ، مرورا بخصوصية التكوين في البناء الديمغرافي العراقي ، وكذا تداعيات وانعكاسات التعددية الطائفية على الامن المجتمعي بعد الاحتلال الامريكي2003 ، والاليات والاستراتيجيات التي تبنتها الحكومة العراقية للحد من اثارها وتحقيق الامن المجتمعي المطلوب . بعد الاحتلال الامريكي سنة 2003. ومن خلال دراستنا للموضوع خلصنا بأن التعددية الطائفية لها الأثر البالغ في حالة اللاأمن الذي يعيشه الشعب العراقي ، وخاصة بعد الاحتلال الامريكي الذي أجج الوضع الطائفي بانتهاجه سياسات تكرس التعددية الطائفية في نظام المحاصصة داخل نظام الحكم في العراق. Abstract: In this study, we dealt with sectarian pluralism and the problematic of building societal security in Iraq, through which we touched on the conceptual framework of sectarian pluralism and community security, passing through the specificity of formation in the Iraqi demographic structure, as well as the repercussions and repercussions of sectarian pluralism on societal security after the US occupation in 2003, and the mechanisms and strategies adopted by the Iraqi government To reduce its effects and achieve the required societal security. After the US occupation in 2003. Through our study of the subject, we concluded that sectarian pluralism has a profound impact on the state of insecurity experienced by the Iraqi people, especially after the American occupation, which inflamed the sectarian situation by adopting policies that reinforce sectarian pluralism in the quota system within the regime in Iraq.
Keywords: التعددية الطائفية-بناء ا-لأمن- المجتمع -العراق